(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2018)
Salesforce motivation has been found to have important consequences for salespeople as well as sales organization. This study analyzes the consequences of salesforce motivation based on the review of studies. The review of studies showed that motivation has an impact on salesforce behavioural and outcome performance, sales territory performance, job satisfaction, adaptive selling, salespeoples’ effort, role conflict, role ambiguity, burnout, salesperson’s effective listening behavior and managerial trust. Based on the findings, research implications are stated.